Internalization Moral Values in Children in TPA and Its Implications for Character Building - Nanik, Nanik (Yayasan Darussalam Bengkulu, 2022)
The aims of this study were to: (1) To determine the concept of internalizing moral values in children at Al-Bayyinah TPA. (2). To find out the process of internalizing moral values in children at Al-Bayyinah TPA. (3). To find out the implications of the process of internalizing moral values in children at Al-Bayyinah TPA on character building. This study uses a qualitative descriptive method with a single research strategy fixed. Sources of data used are informants, places and events, as well as archives and documents. The sampling technique used is purposive sampling. Data collection techniques used are interviews, observation, and document analysis. In this study, validity was obtained by data triangulation techniques and method triangulation, as well as data analysis using interactive analysis, namely (1) data collection, (2) data reduction, (3) data presentation and (4) conclusion drawing. The results of this study can be concluded: (1) The concept of internalizing moral values in children at Al-Bayyinah TPA is with the Vision